2007
DOI: 10.3892/or.18.1.211
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism C3435T of the MDR-1 gene associated with smoking or high body mass index increases the risk of sporadic breast cancer in women

Abstract: Abstract. The human multidrug resistance gene 1 (MDR-1) encodes a plasma membrane P-glycoprotein (P-gp) that functions as the transmembrane efflux pump for various structurally unrelated anticancer agents and toxins. Polymorphisms in the MDR-1 gene may have an impact on the expression and function of P-gp, thereby influencing the susceptibility to various diseases, including cancer. We investigated the incidence of C3435T polymorphisms at exon 26 in the MDR-1 gene in 92 women with breast cancer and potential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…Functional polymorphism C3435T in the MDR1 gene alters the detoxification protective function of Pgp in breast tissue cells exposed to environmental carcinogens in tobacco smoke. This SNP occurs in high incidence among women with breast carcinoma where C allele carriers have increased risk of developing cancer when exposed to toxic substances (35). No significant differences were observed in genotype and allelic frequencies between this publication and the present study.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…Functional polymorphism C3435T in the MDR1 gene alters the detoxification protective function of Pgp in breast tissue cells exposed to environmental carcinogens in tobacco smoke. This SNP occurs in high incidence among women with breast carcinoma where C allele carriers have increased risk of developing cancer when exposed to toxic substances (35). No significant differences were observed in genotype and allelic frequencies between this publication and the present study.…”
Section: Discussioncontrasting
confidence: 49%
“…The results varied in level of statistical significance and role of genotype consequence. Whereas the T/T form was in majority associated with higher risk of disease origin, the carriers of C/C genotype were supposed to have a worse prognosis (35). We did not observe significant differences in this gene polymorphism between patients with breast cancer compared with controls.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Zubor et al (2007), reported that, among patients in Slovak Republic, those carrying CC genotype of C3435T had increased risk of breast cancer. In a study by Macias-Gomez et al (2014) conducted among Mexicans the prevalence of the TT genotype was 8% for patients with fibrocystic changes (FCC), 13% for infiltrating ductal breast cancer (IDBC) and 24% for control samples.…”
Section: Discussionmentioning
confidence: 99%